PELAKSANAAN TUGAS KEPALA DESA DALAM MEMBINA PEREKONOMIAN DESA DI DESA PANGKALAN NYIRIH KECAMATAN RUPAT KABUPATEN BENGKALIS - Ngairi Fitria Ningsih; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Lead the Countryside as existing Governance head in Countryside scope should be able to execute its duty in an optimal fashion, that goodness as society steward and also as medium which can give the solution to problem of arising out in society including area scope becoming tugasnya. Aspiration submitted/sent by society have to be heard by a Countryside head of so that/ to be what becoming target with can be reached is matching with the one which expected. But at field fact still there are a lot of poblems, this matter because of lack of duty execution lead the the countryside. Target of this research is to know the duty execution lead countryside in countryside of river Pangkalan Nyirih distric of rupat sub-province of bengkalis and also factor whai is resistor of duty execution lead countryside in countryside of river of pangkalan nyirih distict of bengkalis sub-province. To analyse the phenemenon in this research is writter use the theory Winardi with the indicator of right time exploiting, sum up the output, readiness to work along, quality of work. Metedologi used in this research research qualitative by using method of Purposive of Sampling. Result of this research show the duty Execution lead countryside in Countryside of River of Pangkalan Nyirih of District of Rupat of Bengkalis Sub-Provinci have been executed better. Adapaun factors found by is sumber daya human being, facilites and basic facilites. Keyword : Duty Execution, Lead Countryside